A macrocyclic oligoelectrolyte as a facial platform for absorbing hyaluronic acid oligomers for targeted cancer cellular imaging. Issue 29 (7th August 2015) - Song, Wenli; Yin, Chao; Jiang, Rongcui; Lu, Xiaomei; Quan, Yiwu; Tian, Congcong; Li, Jie; Hu, Wenbo; Sun, Pengfei; Deng, Weixing; Fan, Quli; Huang, Wei
<x xml:space="preserve">Abstract</x> A macrocyclic oligoelectrolyte with a unique 3D rigid structure modified by hyaluronic acid was developed for targeted cancer cellular imaging, for the first time.